Students’ Perception towards the Use of Worksheet as Helping Tools in Semantics Class - Sri Damayanti; Irwan Irwan; Jusriati Jusriati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
The writer set the problem of this research such as how is the students’ perception toward the use of worksheet as helping tools in semantics class? and what are the advantages of using a worksheet? The aim of this study is to describe the students’ perception of the use of worksheets as helping tools in semantics class and to find the advantages of using it. The subject of this research is the fifth-semester students in the English Department at the University of Cokroaminoto Palopo. The method of this study is a descriptive study. The procedures of collecting data are giving questionnaires and interviews and then the writer analyzed the data by adopting Matthew B. Miles and A. Michael Huberman's pattern. There were three steps; data reduction, data display, and conclusion. After that, the writer tabulated the gained data in making the description of the data. The result of this study shows; (1) Students are giving positive and good perception on the use of worksheet as helping tools in semantics class and (2) The advantage of using the worksheet as helping tools in teaching semantics are; it helped the students in understanding the question and answering the question easily, it also helped them in remembering the past material by using the worksheet and it gave them some motivation to learn English Semantics. So, it can be concluded that the use of worksheets as helping tools in semantics class got a positive response from the students and it also gave them some advantages.